Sciences de la mer - François Grégoire; Alain Caron; Richard Cloutier; Yvon Côté (Le Naturaliste canadien, 2020)
The abundance of Atlantic salmon (Salmo salar) in the North Atlantic has declined significantly in recent decades. Despite substantial efforts to reverse this trend, few stocks have shown signs of recovery. The decreasing number of adult salmon returning to rivers may be due to an increase in natural marine mortality linked to a reduction in growth. The present study aimed to verify whether this hypothesis was supported by two marine phase scalar growth indices (the maximum intercirculi distance attained during the first summer at sea and the total intercirculi distance of the marine growth zone) and the abundance of salmon returning to the Matane River (Québec, Canada). Although the two indices show significant interannual differences, they show an upward trend from 1964 to 1979 and a downward trend from 1995 to 2012. These trends are similar to those of river returns by adult salmon and to the North Atlantic Oscillation Index (NAOI). These similarities support the hypothesis of an inverse relationship between marine growth and mortality, which would subsequently result in variations in abundance. L’abondance du saumon atlantique (Salmo salar) dans le nord de l’Atlantique a diminué considérablement au cours des dernières décennies. Jusqu’à maintenant, peu de stocks ont montré des signes de rétablissement malgré des efforts importants pour renverser cette situation. Les niveaux décroissants d’abondance des saumons adultes de retour en rivière pourraient être associés à une augmentation de la mortalité naturelle en mer découlant d’une réduction de la croissance. La présente étude a pour but de vérifier si 2 indices de croissance scalaire en phase marine (la distance intercirculi maximale atteinte lors de la première saison estivale en mer et la somme des distances intercirculi de la zone de croissance marine des écailles) et l’abondance des retours de saumon dans la rivière Matane (Québec, Canada) appuient cette hypothèse. Bien que ces indices présentent des différences interannuelles significatives, ils ...